Ab-Initio Study of Calcium Fluoride Doped with Heavy Isotopes - Martin Pimon; Andreas Grüneis; Peter Mohn; Thorsten Schumm (Crystals, 2022)
Precision laser spectroscopy of the 229-thorium nuclear isomer transition in a solid-state environment would represent a significant milestone in the field of metrology, opening the door to the realization of a nuclear clock. Working toward this goal, experimental methods require knowledge of various properties of a large band-gap material, such as calcium fluoride doped with specific isotopes of the heavy elements thorium, actinium, cerium, neptunium, and uranium. By accurately determining the atomic structure of potential charge compensation schemes by using a generalized gradient approximation within the ab-initio framework of density functional theory, calculations of electric field gradients on the dopants become accessible, which cause a quadrupole splitting of the nuclear-level structure that can be probed experimentally. Band gaps and absorption coefficients in the range of the 229-thorium nuclear transition are estimated by using the <semantics>G0W0</semantics> method and by solving the Bethe–Salpeter equation.